Evaluasi Frekuensi Penanaman Tanaman Semangka (Citrullus lanatus) Terhadap Keparahan Penyakit dan Produktivitas Tanaman Semangka: Evaluation of Planting Frequency of Watermelon (Citrullus lanatus) Plants on Disease Severity and Productivity of Watermelon - Rizky Randal Cameron; Siti Rakhmi Afriani; Zuhri Multazam; Stenia Ruski Yusticia; Astri Febriani; Robi Saputra (Politeknik Negeri Lampung, 2023)
Watermelon (Citrullus lanatus) is a high-value crop that has been commercially cultivated both in the world and in Indonesia. Many factors affect the productivity of watermelon plants such as land use frequency and plant disease attack. The purpose of this study was to determine the severity of disease in 2 fields with different frequency of planting and the productivity in each of these fields. This research was conducted in June-August 2023 in Tanjung Laut Village, Suak Tapeh District, Banyuasin Regency. The method used in this research is survey method with sampling technique using Simple Random Sampling by taking 216 samples on each land. There were 2 fields used, namely field 1 which was the first time watermelon plants were planted and field 2 which had been planted with watermelon for 3 times (this research was the third time planting). The planting distance used was 0.6 x 4.5 (m). The results of this study are diseases that often attack watermelon plants in this study are anthracnose disease caused by Colletotrichum orbiculare, Cercospora disease caused by Cercospora citrullina, fusarium wilt disease caused by Fusarium sp. and yellow creeping disease. The percentage of anthracnose disease attack in this study was 98.99% in field 1 and in field 2 was 99.06%, which was not significantly different in the T test (P-value 0.93), while the severity of anthracnose disease in field 1 was 46.48% and in field 2 38.99 (P-value 0.0001). Fusarium wilt was the most alarming disease in field 1 at 31.48% and in field 2 at 13.43%. There was an association between the frequency of watermelon planting and the incidence of fusarium wilt disease (P-value 0.00001). Productivity of watermelon plants in field 1 averaged 4.04kg/plant or 14.5 tons/ha while field 2 had a productivity of 5.02/plant or 17.9 tons/ha. The T-test results showed a significant difference between land 1 and land 1 (P-value 0.00003).